Rintisan Pendidikan Anak Usia Dini Suku Tengger di Wilayah Terpencil Dusun Surorowo Desa Kayukebek Kecamatan Tutur Kabupaten Pasuruan - Amang Fathurrohman (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2017)
The limited opportunities and access to education in the village of Surorowo compared to other sub-villages, forcing the Surorowo people to access education easily. Therefore, the community development program for Early Childhood Education is one of the efforts to improve education access for children in Surorowo village. By using Community Based Research (CBR) method, this community development effort has successfully initiated the establishment of Early Childhood Education. In its implementation many obstacles are faced, such as limited human resources, infrastructure, and institutional management experience. But the spirit of Surorowo people in improving the quality of education for their children is very high, so the limitations that exist do not become a barrier for parents to prepare for a better generation.Kata Kunci: Early Childhood Education, Community Based Research (CBR), Suku Tengger.